1966
DOI: 10.1210/endo-79-3-511
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Thyroid Physiology During Pneumococcal Septicemia in the Rat1

Abstract: A QABSTRACT. The impact of acute infection on iodine concentration was decreased. Kidney thyroid physiology was investigated in rats inradioactivity in the T3 and T 4 groups was unfccted with a type-specific pneumococcus. Inchanged by infection. Although infection altered fected rats showed a lower thyroidal 13I uptake bowel motility, with a resultant delay in the apCc than healthy controls at all time periods studied. pearance of radioactivity in the colon of rata Unlike in the rat, thyroidal 131 uptake curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

1967
1967
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 2 publications
1
20
1
Order By: Relevance
“…In earlier studies, an increase of the fractional rate of To turnover [(k)] has been observed during infectious illness in rats (2), monkeys (5), and man (1,3,4), although Wiswell and Coronho noted no change in Ts turnover in volunteers given typhoid fever (21). A decrease in T4 turnover has been observed only after surgical stress (22,23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier studies, an increase of the fractional rate of To turnover [(k)] has been observed during infectious illness in rats (2), monkeys (5), and man (1,3,4), although Wiswell and Coronho noted no change in Ts turnover in volunteers given typhoid fever (21). A decrease in T4 turnover has been observed only after surgical stress (22,23).…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION Studies of thyroid function during infection in animals and man have yielded a variety of results. The prepon--derance of data, however, suggests that peripheral thyroxine (T4) turnover is increased (1)(2)(3)(4)(5), and that thy- roid function is generally depressed initially, and then often rebounds during recovery from the infectious illness (6)(7)(8)(9). The great majority of these earlier studies depended either upon the use of epithyroid counting to estimate the rate of release of glandular hormonal iodine, or upon measurement of the concentration of serum PB"1I with time after the injection of labeled T4, in order to assess peripheral To metabolism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukocytes isolated from blood obtained Received for publication 9 July 1970 and in revised form 7 November 1970. ronine (TB) in several animal species, the results of such studies tend to be conflicting, appearing to vary with the nature of the species examined. In the rat, for example, acute streptococcal and pneumococcal infections appear to result in a depression of thyroid function (1,2), whereas in man data obtained after treatment of acute pneumococcal pneumonia had been instituted suggest that an increase in thyroid function might accompany this type of stress (3).…”
mentioning
confidence: 99%
“…Additionally, the depressed plasma concentrations of thyroid hormones fail to stimulate the secretion of thyroid-stimulating hormone (TSH), thus indicating an impairment in the pituitary-thyroid feedback system Shambaugh-Beisel, 1966). These abnormalities are the result of cytokineinduced alterations at all levels of this system .…”
Section: Hypothalamic-pituitary-thyroid Systemmentioning
confidence: 99%